2019
DOI: 10.4103/jips.jips_277_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of elastic recovery of three different elastomeric impression materials on chemical disinfection and autoclaving: An in vitro study

Abstract: Aim: The aim of the study was to investigate the effect of disinfection and steam autoclaving on the elastic recovery of three different elastomeric impression materials. Settings and Design: In vivo - comparative study. Materials and Methods: Ninety dumbbell-shaped specimens of commercially available two addition-cured silicones (AFFINIS and AQUASIL) and one condensation-cured silicone (SPEEDEX) impression materials were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In particular, polyvinyl siloxanes (PVS, addition silicones) are characterized by high elastic recovery and are resistant to tearing and deformation. They are almost ideal elastic impression materials with 99.9% of elastic recovery (while for condensation silicones, it ranges between 98.2% and 99.6%) [ 22 ]. Demajo et al demonstrated that silicone impression material exhibited a significantly lower microbial count than alginate material [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, polyvinyl siloxanes (PVS, addition silicones) are characterized by high elastic recovery and are resistant to tearing and deformation. They are almost ideal elastic impression materials with 99.9% of elastic recovery (while for condensation silicones, it ranges between 98.2% and 99.6%) [ 22 ]. Demajo et al demonstrated that silicone impression material exhibited a significantly lower microbial count than alginate material [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity of sodium hypochlorite is related to the presence of chlorine, which inhibits essential bacterial enzymes, leading to irreversible enzymatic inactivation in bacteria and lipid and fatty acid degradation ( Estrela et al, 2002 ). However, it should be emphasized that this procedure ensures disinfection rather than complete sterilization ( Gothwal et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Elastic recovery is the ability of an elastic material to return to its original shape after being deformed inside the mouth with negligible permeant deformation. The higher the elastic recovery of a material, the more precise the final restoration will be [7]. Moreover, tear energy is very important, especially in taking impressions in thin areas.…”
Section: Introductionmentioning
confidence: 99%